2019
DOI: 10.1002/jcla.23016
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune‐inflammation index acts as a novel diagnostic biomarker for postmenopausal osteoporosis and could predict the risk of osteoporotic fracture

Abstract: Abbreviations: BMD, bone mineral density; BMI, body mass index; CI, confidence interval; DEXA, dual-energy X-ray absorptiometry; HR, hazard ratio; LMR, lymphocyte-to-monocyte ratio; MCH, mean corpuscular hemoglobin; MCHC, mean corpuscular hemoglobin concentration; NLR, neutrophil-to-lymphocyte ratio; OR, odds ratio; PDW, platelet distribution width; PLR, platelet-to-lymphocyte ratio; PMOP, postmenopausal osteoporosis; RDW, red blood cell distribution width; SII, systemic immune-inflammation index. AbstractBack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 29 publications
(29 reference statements)
3
76
1
1
Order By: Relevance
“…In a study of postmenopausal Korean women, it was shown that NLR was negatively associated with the mean lumbar BMD [26]. In a report of a large group of postmenopausal women, Fang et al observed that NLR was an independent risk factor for postmenopausal osteoporosis [34]. Moreover, several studies have shown that an elevated NLR was associated with poor prognosis in osteoporotic individuals [5,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of postmenopausal Korean women, it was shown that NLR was negatively associated with the mean lumbar BMD [26]. In a report of a large group of postmenopausal women, Fang et al observed that NLR was an independent risk factor for postmenopausal osteoporosis [34]. Moreover, several studies have shown that an elevated NLR was associated with poor prognosis in osteoporotic individuals [5,27].…”
Section: Discussionmentioning
confidence: 99%
“…NLR and PLR were reported to be closely related to systemic inflammation and immune response status [34]. Recent data showed that raised NLR and/or PLR were associated with i.a.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic immune-inflammation index (SII), which is a composite indicator integrating platelet, neutrophil and lymphocyte counts, has been proven to be a promising prognostic predictor in various diseases, including malignant tumors [ 20 22 ], coronary artery disease [ 23 ], acute ischemic stroke [ 24 ], and preterm premature rupture of the membranes [ 25 ]. Moreover, high SII (≥834.89) was newly identified as a good risk predictor for discriminating osteoporotic fracture risk in postmenopausal osteoporosis patients [ 26 ]. Recently, we also firstly reported that high platelet-to-lymphocyte ratio (PLR) was associated with increased 1 year all-cause mortality in older adults with hip fracture [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It takes two aspects, inflammation and immunity, into consideration. Someone assumed that good performance of SII might owe to the integration of three indexes, which avoid being easily affected by individual differences and show greater stability ( 2 , 21 , 36 ). That may be exactly the same as SIRI.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent few years, the exacerbation of COPD has become the focus of our attention. It contributed to a series of problems ( 2 , 3 )—worsening lung function, decreasing life quality ( 4 , 5 ), accelerating disease progress, and elevating the risk of hospitalization or mortality ( 3 , 6 , 7 ). Recently, the use of hemogram indexes indicating systemic inflammation has been determined in clinical practice for predicting hospitalization and mortality in COPD.…”
Section: Introductionmentioning
confidence: 99%